A study on the catalytic synergism between K and Pd in Co3Al(O) hydrotalcite-derived oxide catalysts used for soot combustion. (2nd October 2015) - Liu, Dongsheng; Guo, Xin; Meng, Ming; Zhang, Yuxia; Jiang, Zheng
Abstract: The K/Co3− x Pd x Al(O) ( x =0 or 0.02) and K/Pd/Co3 Al(O) catalysts promoted by K and Pd were synthesized by using pH-constant co-precipitation and successive impregnation methods through the precursors of hydrotalcites. The physicochemical properties of these catalysts were systematically characterized by XRD, EXAFS, XANES, XPS, HRTEM, H2 -TPR, soot-TPR and in-situ FT-IR. It is found that the catalyst K/Pd/Co3 Al(O) prepared by successive impregnation displays the lowest characteristic temperatures including the initial and final combustion temperatures ( T i and T f ). The coexistence of K and Pd in K/Pd/Co3 Al(O) or K/Co3− x Pd x Al(O) can improve both the reducibility and the oxidizability of the catalysts, generating a prominent catalytic synergism on soot oxidation. K–Co–O and K–Pd–O have been identified as the main active phases in the catalysts simultaneously promoted by K and Pd. Based on the results of in-situ FT-IR three potential reaction pathways for soot combustion have been revealed, namely the direct soot oxidation, nitrate-enhanced soot oxidation and NO2 -assisted soot oxidation. As compared with the conventional Pd/Al2 O3 catalyst, the as-prepared K/Pd/Co3 Al(O) catalyst possesses much higher thermal stability. Highlights: The Co3 Al(O) catalyst promoted by K and Pd is highly efficient for soot oxidation. A prominent catalytic synergism between K and Pd on soot oxidation is observed. K–Co–O and K–Pd–O are identified as the main active phases for soot combustion. Three reaction pathways for soot combustion are revealed by in-situ FT-IR.